Numerical simulation of the aeroelastic interaction between compressor blade and subsonic airflow in three-dimensional approach - Rusakov, Sergey Vladimirovich; Shuvaev, Nikolay Vasilievich (Computational Continuum Mechanics, 2013)
Numerical stability analysis of the vibrating compressor blade in subsonic airflow has been made. Two techniques are applied: energetic approach (calculation of the work done by gas forces per blade oscillation cycle) and direct numerical simulation (conjugate problem solution). Calculations are performed in three-dimensional approach using ANSYS CFX and ANSYS Mechanical v. 13. Blade surface displacements are taken into account by applying a moving mesh which is deformed at each time step by means of a user routine.
Keywords: blade flutter; ANSYS CFX; ANSYS Mechanical